Complete Wafer Physical Quality Test Based On Mung Bean Sprout Husk Waste - Wijaya, Dewi; Safitri, Apdila; Anjani, Fandini Meilia; Ardiansyah, Ardiansyah (CV. Komunitas Dunia Peternakan, 2025)
Mung bean sprout husk is waste with promising nutritive value (crude protein 14%, Total Digestible Nutrients 64.58%, moisture 63.35%) and, due to its high moisture, is suitable for processing via feed-wafer technology. This study aimed to evaluate the physical quality and identify the best storage duration of complete wafers formulated with mung bean sprout husk. A completely randomized design with four treatment levels (0%, 10%, 20%, 30%) and three replicates was used. Organoleptic traits were described descriptively, while physical traits density, water absorption, impact resistance, and wafer durability index (WDI) were analyzed by one-way ANOVA followed by Duncan’s Multiple Range Test (α = 0.05). Supplementation of mung bean sprout husk significantly affected density and water absorption (P < 0.05), with the 30% treatment achieving the highest density (0.57 g·cm⁻³) and water absorption (83.0%), both superior to the control (P < 0.05). In contrast, impact resistance (99.1%) and WDI (85.8%) did not differ among treatments (P > 0.05). Overall, the 30% supplementation delivered the best physical quality and the best storage duration among the tested formulations.